Existence of Bov-B LINE Retrotransposons in Snake Lineages Reveals Recent Multiple Horizontal Gene Transfers with Copy Number Variation - Puinongpo, Weerada (Genes (Basel), 2020)
Transposable elements (TEs) are dynamic elements present in all eukaryotic genomes. They can “jump” and amplify within the genome and promote segmental genome rearrangements on both autosomes and sex chromosomes by disruption of gene structures. The Bovine-B long interspersed nuclear element (Bov-B LINE) is among the most abundant TE-retrotransposon families in vertebrates due to horizontal transfer (HT) among vertebrate lineages. Recent studies have shown multiple HTs or the presence of diverse Bov-B LINE groups in the snake lineage. It is hypothesized that Bov-B LINEs are highly dynamic and that the diversity reflects multiple HTs in snake lineages. Partial sequences of Bov-B LINE from 23 snake species were characterized. Phylogenetic analysis resolved at least two Bov-B LINE groups that might correspond to henophidian and caenophidian snakes; however, the tree topology differed from that based on functional nuclear and mitochondrial gene sequences. Several Bov-B LINEs of snakes showed greater than 80% similarity to sequences obtained from insects, whereas the two Bov-B LINE groups as well as sequences from the same snake species classified in different Bov-B LINE groups showed sequence similarities of less than 80%. Calculation of estimated divergence time and pairwise divergence between all individual Bov-B LINE copies suggest invasion times ranging from 79.19 to 98.8 million years ago in snakes. Accumulation of elements in a lineage-specific fashion ranged from 9 × 10(−6)% to 5.63 × 10(−2)% per genome. The genomic proportion of Bov-B LINEs varied among snake species but was not directly associated with genome size or invasion time. No differentiation in Bov-B LINE copy number between males and females was observed in any of the snake species examined. Incongruence in tree topology between Bov-B LINEs and other snake phylogenies may reflect past HT events. Sequence divergence of Bov-B LINEs between copies suggests that recent multiple HTs occurred within the same evolutionary timeframe in the snake lineage. The proportion of Bov-B LINEs varies among species, reflecting species specificity in TE invasion. The rapid speciation of snakes, coinciding with Bov-B LINE invasion in snake genomes, leads us to better understand the effect of Bov-B LINEs on snake genome evolution.